Proteomic analysis of formalin-fixed paraffin-embedded glomeruli suggests depletion of glomerular filtration barrier proteins in two-kidney, one-clip hypertensive rats - Finne, Kenneth (Nephrol Dial Transplant, 2014)
BACKGROUND: It is well known that hypertension may cause glomerular damage, but the molecular mechanisms involved are still incompletely understood. METHODS: In the present study, we used formalin-fixed paraffin-embedded (FFPE) tissue to investigate changes in the glomerular proteome in the non-clipped kidney of two-kidney one-clip (2K1C) hypertensive rats, with special emphasis on the glomerular filtration barrier. 2K1C hypertension was induced in 6-week-old Wistar Hannover rats (n = 6) that were sacrificed 23 weeks later and compared with age-matched sham-operated controls (n = 6). Tissue was stored in FFPE tissue blocks and later prepared on tissue slides for laser microdissection. Glomeruli without severe morphological damage were isolated, and the proteomes were analysed using liquid chromatography–tandem mass spectrometry. RESULTS: 2K1C glomeruli showed reduced abundance of proteins important for slit diaphragm complex, such as nephrin, podocin and neph1. The podocyte foot process had a pattern of reduced abundance of transmembrane proteins but unchanged abundances of the podocyte cytoskeletal proteins synaptopodin and α-actinin-4. Lower abundance of important glomerular basement membrane proteins was seen. Possible glomerular markers of damage with increased abundance in 2K1C were transgelin, desmin and acyl-coenzyme A thioesterase 1. CONCLUSIONS: Microdissection and tandem mass spectrometry could be used to investigate the proteome of isolated glomeruli from FFPE tissue. Glomerular filtration barrier proteins had reduced abundance in the non-clipped kidney of 2K1C hypertensive rats.